Ideological, Political and Economic Changes in Central Europe (Czech Journal of International Relations, 2024)
Der schwierige Selbstfindungsprocess. Regionalismen - Nationalismen - Reideologisierung. Kolektiv autorů. Hg. Peter Gerlich, Krzysztof Glass. Wiell - Österreichische Gesellschaft für Mitteleuropďische Studien, Toruň – Wydawnictwo Adam Marszalek, 1995, 257 stran, ISBN 3-901449-55-8, 83-86229-79-9.